Upper Semicontinuity of Solution Mappings to Parametric Generalized Vector Quasiequilibrium Problems - Shu-qiang Shan; Yu Han; Nan-jing Huang (Journal of Function Spaces)
We establish the upper semicontinuity of solution mappings for a class of parametric generalized vector quasiequilibrium problems. As applications, we obtain the upper semicontinuity of solution mappings to several problems, such as parametric optimization problem, parametric saddle point problem, parametric Nash equilibria problem, parametric variational inequality, and parametric equilibrium problem.